Waste Management Governance In Muara Satu District, Lhokseumawe City - Maya Rahma Yanti Siregar; Akmal Akmal; Risna Dewi; Sufi Sufi; Asrul Fahmi (Indonesian Journal Economic Review (IJER), 2026)
Waste management remains a critical environmental challenge in Indonesian urban areas, with governance failures contributing to persistent issues including illegal dumping and inadequate infrastructure. This study examines waste management governance in Muara Satu District, Lhokseumawe City, analyzing implementation through five principles of good governance: participation, rule of law, transparency, responsiveness, and accountability, while identifying obstacles to effective management. A qualitative descriptive approach was employed, utilizing observation, in-depth interviews with eight purposively and accidentally selected informants, and documentation. Data analysis followed the Miles and Huberman interactive model, with data validity ensured through source and technique triangulation. The findings reveal that waste management governance has not achieved optimal implementation. Community participation remains transactional and limited to economic incentives. Rule of law enforcement is weak despite existing Qanun Number 9 of 2015, with inconsistent sanctions and persistent illegal waste sites. Transparency is partial, with program information available but budget information undisclosed. Responsiveness shows mixed results: while the Environmental Agency has developed innovative processing technologies, operational constraints limit timely service delivery. Accountability operates predominantly through vertical mechanisms, with limited horizontal accountability to communities. Two categories of obstacles were identified: structural constraints including inadequate fleet capacity (39 vehicles serving 133 tons daily waste), damaged equipment, limited storage sites, and insufficient human resources; and cultural constraints including low community awareness, limited participation, and entrenched habits. These obstacles are mutually reinforcing, creating a feedback loop that perpetuates governance weaknesses. Strengthening governance requires simultaneous investment in infrastructure, consistent enforcement, comprehensive transparency, proactive responsiveness, and systematic accountability mechanisms.